2014
DOI: 10.1037/spq0000009
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and confirmatory factor analyses of the WISC-IV with gifted students.

Abstract: These 2 studies investigated the factor structure of the Wechsler Intelligence Scale for Children-4th edition (WISC-IV; Wechsler, 2003a) with exploratory factor analysis (EFA; Study 1) and confirmatory factor analysis (CFA; Study 2) among 2 independent samples of gifted students. The EFA sample consisted of 225 children who were referred for a cognitive assessment as part of the application for gifted programming in their schools. The CFA sample consisted of 181 students who were tested the following year. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…The second order four-factor model obtained very similar results to the first order results, although its χ² value was slightly higher. Therefore, Rowe et al (2014) concluded that the results supported the first order four-factor solution of the WISC-IV, which establishes the general structure of the scale for gifted children.…”
mentioning
confidence: 78%
“…The second order four-factor model obtained very similar results to the first order results, although its χ² value was slightly higher. Therefore, Rowe et al (2014) concluded that the results supported the first order four-factor solution of the WISC-IV, which establishes the general structure of the scale for gifted children.…”
mentioning
confidence: 78%
“…Prifitera, Saklofske, and Weiss (2005) suggested that the collection of such information may be conducive to the optimal interpretation of test results. Among traditional ability tests, the Stanford-Binet Intelligence Scale appears to have the longest history (Rowe, Dandridge, Pawlush, Thompson, & Ferrier, 2014). Based on large normative samples of individuals, the Stanford-Binet Intelligence Scale measures the cognitive performance of individuals across the life span on five cognitive factors that are broadly based on the CHC hierarchical model: knowledge, quantitative reasoning, visual-spatial processing, working memory, and fluid reasoning (Naglieri, 2008;Newton, McIntosh, Dixon, Williams, & Youman, 2008).…”
Section: Ability Testsmentioning
confidence: 99%
“…In comparison, the Wechsler family of tests, and particularly the Wechsler Intelligence Scale for Children (WISC), have been recognized as being the most commonly used ability tests for the identification of gifted students (Rowe et al, 2014). Unlike other traditional ability tests, the Wechsler family of tests is comprised of three different individual tests to be administered with different age groups: Wechsler Preschool and Primary Scale of Intelligence (WPPSI; 2:7 to 7:7 years old), the WISC (6:00 to 16:11years old), and the Wechsler Adult Intelligence Scale (WAIS; 16:00 to 90:11 years old).…”
Section: Ability Testsmentioning
confidence: 99%
“…Volume 29, number 4 also included general articles about the use and barriers to using evidence-based interventions in the schools (Hicks et al, 2014), evaluation of flu ency gains related to a performance feedback writing intervention (Hier & Eckert, 2014), whether fear appeals predict motivation and exam scores (Putwain & Remedios, 2014), measuring engagement among school-age chil dren grades four through 12 (Wang, Bergin, & Bergin, 2014), exploratory and confirmatory factor analysis of the WISC-IV with gifted stu dents (Rowe et al, 2014), the association of life satisfaction and maladaptive behaviors in early adolescents (Lyons et al, 2014), and the use of a culturally adapted version of the Strong Teens program to promote socialemotional learning in adolescent Latino Eng lish Language Learners (Castro-Olivo, 2014).…”
Section: The Diversity Of Topics Featured In School Psychology Quarterlymentioning
confidence: 99%